Beyond access: Structural and pedagogical barriers to e-learning in South African higher education - Molokomme, Radiakga Thabang (Edelweiss Applied Science and Technology, 2026)
The rapid expansion of e-learning in higher education has been widely regarded as a mechanism for enhancing access and flexibility. However, in contexts characterized by socio-economic inequality, such as South Africa, this transition has exposed persistent structural and pedagogical challenges that undermine its effectiveness. This study aimed to examine the structural barriers influencing students’ access to and participation in e-learning, the pedagogical challenges affecting its effectiveness, and how these factors collectively shape students’ learning experiences and outcomes within a university of technology. A qualitative research approach was employed, utilizing semi-structured interviews with 20 undergraduate students selected through purposive sampling. Data were analyzed using thematic analysis. The findings reveal that structural barriers, including limited access to reliable internet, high data costs, inadequate devices, and unconducive learning environments, significantly constrain student participation. In addition, pedagogical challenges, such as passive content delivery, limited interaction, delayed feedback, and inconsistent use of digital tools, hinder meaningful engagement. Importantly, the study demonstrates that these barriers are not isolated but mutually reinforcing, resulting in compounded disadvantages for students. The study contributes to the literature by providing a nuanced, student-centered understanding of e-learning challenges and extending theoretical perspectives on the digital divide and technology acceptance in resource-constrained contexts. It is recommended that higher education institutions adopt integrated strategies that address both infrastructural inequalities and pedagogical design to enhance the effectiveness and inclusivity of e-learning.